A Novel Decision-Making Process in the Environment of Generalized Version of Fuzzy Sets for the Selection of Energy Source. (23rd August 2022) - Madasi, Joseph David; Khan, Salma; Kausar, Nasreen; Pamucar, Dragan; Addis, Gezahagne Mulat; Gulistan, Muhammad
Abstract : In this study, we focus our attention on a kind of generalized fuzzy set. This generalized fuzzy set is known as neutrosophic octahedron sets (NOSs). NOSs are a combination of neutrosophic, intuitionistic fuzzy, and octahedron sets that provide a better platform for dealing with imprecise and ambiguous data. First of all, we analyze uncertainty, for this purpose, we need neutrosophic octahedron set that can also reduce the loss of information about ambiguity and uncertainty. We use NOS over TOPSIS method (technique to order the performance by similarity with the ideal solution). It is a most suitable technique for describing uncertain data in the TOPSIS method in order to allow more imprecision than the neutrosophic, intuitionistic fuzzy, and octahedron set. Thus, the TOPSIS method of NOSs in decision making is used to overcome the problems that arise during decision-making. We use this proposed structure to implement the selection of the energy source by a numerical example as an application. As a result, this model is valuable for decision-making and can be used to choose the most environmentally friendly energy source. Finally, we present an example to demonstrate the validity and effectiveness of the proposed strategy.